PERAN PENDIDIKAN TERHADAP MORAL PESERTA DIDIK - Agung Mandala Putra; Mardiah Astuti; Karoma Karoma (EDUCATIONAL JOURNAL : General and Specific Research, 2023)
The issue of forming the moral character of students is an issue that continues to be voiced in the world of education. However, students as objects that are formed require assistance from stakeholders. Stakeholders are not only educators such as teachers in schools, but also parents. However, nowadays an educator is in the spotlight, as if he is a milestone that can shape an individual's moral character. Related to the notion of educators as a pillar of individual moral formation, this makes it a challenge to create moral individuals as the Indonesian generation.